Improved mitochondrial function in brain aging and Alzheimer disease - the new mechanism of action of the old metabolic enhancer piracetam - Leuner, Kristina; Kurz, Christopher; Guidetti, Giorgio; Orgogozo, Jean-Marc; Müller, Walter E. (Frontiers in Neuroscience, 2010)
Piracetam, the prototype of the so-called nootropic drugs’ is used since many years in different countries to treat cognitive impairment in aging and dementia. Findings that piracetam enhances fluidity of brain mitochondrial membranes led to the hypothesis that piracetam might improve mitochondrial function, e.g. might enhance ATP synthesis. This assumption has recently been supported by a number of observations showing enhanced mitochondrial membrane potential (MMP), enhanced ATP production, and reduced sensitivity for apoptosis in a variety of cell and animal models for aging and Alzheimer disease (AD). As a specific consequence, substantial evidence for elevated neuronal plasticity as a specific effect of piracetam has emerged. Taken together, these new findings can explain many of the therapeutic effects of piracetam on cognition in aging and dementia as well as different situations of brain dysfunctions.